Current Advances in Immune Checkpoint Inhibition and Clinical Genomics in Upper Tract Urothelial Carcinoma: State of the Art - Gianluigi Califano; Idir Ouzaid; Paul Laine-Caroff; Arthur Peyrottes; Claudia Collà Ruvolo; Benjamin Pradère; Vincent Elalouf; Vincent Misrai; Jean-François Hermieu; Shahrokh F. Shariat; Evanguelos Xylinas (Current Oncology, 2022)
Upper tract urothelial carcinoma (UTUC) is a rare and challenging-to-treat malignancy. In most patients it is a sporadic tumor entity, less commonly it falls on the spectrum of Lynch syndrome, an autosomal dominant familial tumor syndrome. Localized UTUC with high-risk features as well as the metastatic disease scenario might require systemic therapy. Platinum-based combination chemotherapy is currently the recommended management option. However, the introduction of immune checkpoint inhibitors into the therapeutic armamentarium has led to a paradigm shift in treatment standards. Immunotherapy has been shown to be safe and effective in treating at least metastatic UTUC, although UTUC-specific high-level evidence is still lacking. Recent technological advances and noteworthy research efforts have greatly improved the general understanding of the biological landscape of UTUC. According to the main findings, UTUC represent a particular subtype of urothelial carcinoma frequently associated with activated FGFR3 signaling, a luminal–papillary phenotype and a T-cell-depleted microenvironment. This improved knowledge promises precision oncology approaches that match treatment decision strategies and genomic profile to ultimately result in better clinical outcomes. The aim of this review was to summarize the main currently available evidence on immune checkpoint inhibition and clinical genomics in UTUC.